ANALISIS EFISIENSI PENGGUNAAN MODAL KERJA PERUSAHAAN DENGAN RASIO KEUANGAN - Yulitiawati Yulitiawati; Desy Mandela (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
The data analysis technique used is descriptive analysis. Based on the results ofthe study, it shows that in PT. Semen Baturaja, company current ratio is always in goodcondition which is more than 100 that the company is very capable in paying short-termobligations on time. And the capital issued, the company is able to manage capital well sothat loans can be paid on time. Debt to equity ratio of the company shows that everycapital used by PT. Semen Baturaja is widely is used by its own capital. Debt to assetratio shows that the profits owned by the company through the assets of PT. SemenBaturaja Tbk, it uses its own capital to increase the company's assets and profits. Theratio of company return on assets often decreases. The return on equity ratio shows thatthe company has the advantage of decreasing capital management. Whereas net profitmargin shows decrease in profits to be very small and continues to decline. Inventoryturnover ratio shows that the company is able to manage the existing capital while stillaccelerating the inventory turnover in the company. Accounts receivable turnover of thecompany has number that continues to decrease significantly which gives an illustrationthat the company's assets are not filled with receivables and the company has actualassets in every period.